2024
DOI: 10.3390/vetsci11030113
|View full text |Cite
|
Sign up to set email alerts
|

Short Road Transport and Slaughter Stress Affects the Expression Profile of Serotonin Receptors, Adrenocortical, and Hematochemical Responses in Horses

Giuseppe Bruschetta,
Gabriella Zanghì,
Renato Paolo Giunta
et al.

Abstract: Horse transport is considered a cause of stress in animals and is known to affect the 5-HT concentrations in both the brain and other tissues. The aim of this research was to investigate the effect of horse transportation and slaughter stress on plasma serotonin’s concentration and the expression levels of the related 5-HT1B and 5-HT2A receptors in PBMCs. Furthermore, the IL-12 levels and a variety of blood parameters, including triglycerides, total cholesterol, glucose, aspartate aminotransferase, creatine ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…In this regard, HPA activation is one of the most important neuroendocrine responses that occurs, promoting the restoration of the body's homeostasis. Many studies showed cortisol rising following transport [5,42,[54][55][56]. These results depend on the habit of the horses, their age and experience, the duration of transport, the environmental conditions and transport management itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, HPA activation is one of the most important neuroendocrine responses that occurs, promoting the restoration of the body's homeostasis. Many studies showed cortisol rising following transport [5,42,[54][55][56]. These results depend on the habit of the horses, their age and experience, the duration of transport, the environmental conditions and transport management itself.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, high cortisol values after transport have been shown in foals during their first experiences over both short and long distances [54,57], in stallions [2] and in racehorses during both long and short journeys [42]. The lack of previous transport experience in subjects used for meat production as opposed to athletic horses used to being transported for competitions presumably contributed to the significant increase in blood cortisol levels detected after transport and slaughter [56]. This may explain the present findings, indicating that cortisol concentration was maintained during the various transport phases.…”
Section: Discussionmentioning
confidence: 99%
“… 2016 ; Bruschetta et al. 2024 ). The use of a balanced anesthetic protocol could reduce the anesthetics dose with an effective reduction in the side effects induced by surgical stress (Beloeil and Nouette-Gaulain 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, acute stress can induce increases or decreases in serotonin concentrations (Bruschetta et al. 2024 ).…”
Section: Introductionmentioning
confidence: 99%